Major glucuronide metabolites of testosterone are primarily transported by MRP2 and MRP3 in human liver, intestine and kidney. Issue 191 (July 2019) - Li, Cindy Yanfei; Basit, Abdul; Gupta, Anshul; Gáborik, Zsuzsanna; Kis, Emese; Prasad, Bhagwat
Abstract: Testosterone glucuronide (TG), androsterone glucuronide (AG), etiocholanolone glucuronide (EtioG) and dihydrotestosterone glucuronide (DHTG) are the major metabolites of testosterone (T), which are excreted in urine and bile. Glucuronides can be deconjugated to active androgen in gut lumen after biliary excretion, which in turn can affect physiological levels of androgens. The goal of this study was to quantitatively characterize the mechanisms by which TG, AG, EtioG and DHTG are eliminated from liver, intestine, and kidney utilizing relative expression factor (REF) approach. Using vesicular transport assay with recombinant human MRP2, MRP3, MRP4, MDR1 and BCRP, we first identified that TG, AG, EtioG, and DHTG were primarily substrates of MRP2 and MRP3, although lower levels of transport were also observed with MDR1 and BCRP vesicles. The transport kinetic analyses revealed higher intrinsic clearances of TG by MRP2 and MRP3 as compared to that of DHTG, AG, and EtioG. MRP3 exhibited higher affinity for the transport of the studied glucuronides than MRP2. We next quantified the protein abundances of these efflux transporters in vesicles and compared the same with pooled total membrane fractions isolated from human tissues by quantitative LC–MS/MS proteomics. The fractional contribution of individual transporters (ft ) was estimated by proteomics-based physiological scaling factors, i.e., transporter abundance in whole tissue versus vesicles, and corrected for inside-out vesicles (determined by 5′-nucleotidase assay). The glucuronides of inactive androgens, AG and EtioG were preferentially transported by MRP3, whereas the glucuronides of active androgens, TG and DHTG were mainly transported by MRP2 in liver. Efflux by bile canalicular transport may indicate the potential role of enterohepatic recirculation in regulating the circulating active androgens after deconjugation in the gut. In intestine, MRP3 possibly contributes most to the efflux of these glucuronides. In kidney, all studied glucuronides seemed to be preferentially effluxed by MRP2 and MDR1 (for EtioG). These REF based analysis need to be confirmed with in vivo findings. Overall, characterization of the efflux mechanisms of T glucuronide metabolites is important for predicting the androgen disposition and interindividual variability, including drug-androgen interaction in humans. The mechanistic data can be extrapolated to other androgen relevant organs (e.g. prostate, testis and placenta) by integrating these data with quantitative tissue proteomics data.